Oscillation Results for a Class of Nonlinear Fractional Order Difference Equations with Damping Term. (1st June 2020) - Selvam, A. George Maria; Alzabut, Jehad; Jacintha, Mary; Özbekler, Abdullah
Abstract : The paper studies the oscillation of a class of nonlinear fractional order difference equations with damping term of the form Δ ψ λ z η λ + p λ z η λ + q λ F ∑ s = λ 0 λ − 1 + μ λ − s − 1 − μ y s = 0, where z λ = a λ + b λ Δ μ y λ, Δ μ stands for the fractional difference operator in Riemann-Liouville settings and of order μ, 0 < μ ≤ 1, and η ≥ 1 is a quotient of odd positive integers and λ ∈ ℕ λ 0 + 1 − μ . New oscillation results are established by the help of certain inequalities, features of fractional operators, and the generalized Riccati technique. We verify the theoretical outcomes by presenting two numerical examples.